1999
DOI: 10.1086/515146
|View full text |Cite
|
Sign up to set email alerts
|

Late Cytomegalovirus Pneumonia in Adult Allogeneic Blood and Marrow Transplant Recipients

Abstract: To assess the impact of antiviral prophylaxis during the first 3 months after transplantation on the frequency, timing, and outcome of cytomegalovirus (CMV) pneumonia during the first year, 541 adult allogeneic blood and marrow transplant recipients were evaluated. Thirty-four patients (6.3%) developed 35 episodes of CMV pneumonia at a mean of 188 days after transplantation, with an associated mortality rate of 76%. Twenty-six episodes (74%) occurred late (after day 100). Of the patients with late CMV pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 6 publications
5
84
0
1
Order By: Relevance
“…[3][4][5][6]8 These data suggest that the extended AG surveillance performed in our study, may have played an important role in preventing the development of late CMV disease.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…[3][4][5][6]8 These data suggest that the extended AG surveillance performed in our study, may have played an important role in preventing the development of late CMV disease.…”
Section: Discussionmentioning
confidence: 87%
“…[1][2][3] Both strategies focused on the first 100 days after transplantation and after that most of the published series have screened for CMV infection or disease only in the presence of symptoms. [3][4][5][6][7] Therefore, few surveillance data are available on the occurrence of CMV infection and recurrences after day +100. 8 However, some reports have suggested that the prolonged use of ganciclovir may inhibit the development of CMV-specific T cell responses promoting the occurrence of CMV infection and disease after discontinuation of antiviral therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25] (5) Late-onset CMV pneumonia has emerged as an important complication. 26,27 In a prior study, one-third of late viral infections were caused by CMV, and CMV was responsible for 57% of late life-threatening viral infections. 5 In the current study, two-thirds of late viral pneumonias were caused by CMV, and most of these first late episodes occurred within the first year after discharge home.…”
Section: Discussionmentioning
confidence: 99%
“…Le strategie miranti alla prevenzione dell'infezione da CMV prevedono anche l'uso di una terapia preemptiva guidata dalla determinazione della CMV viremia (1,4,7). Tuttavia la malattia da CMV ancora si manifesta particolarmente nei pazienti sottoposti a trapianto di midollo che sviluppano Graft versus host disease (GVHD) o che vengono sottoposti a profilassi antivirale prolungata durante l'immediato periodo post trapianto (6). Da quanto esposto è evidente come i miglioramenti tecnologici della diagnostica virologica siano di estrema importanza e costituiscano un valido aiuto ai fini del successo nella prevenzione dell'infezione da CMV; in particolare l'introduzione della determinazione quantitativa del CMV-DNA ha contribuito maggiormente a tale successo soprattutto per ciò che riguarda la possibilità da parte del clinico di modulare la terapia in base ai dati di laboratorio…”
Section: Introduzioneunclassified